Effects of elemental composition variations of Keggin polyoxometalates on photocurrent generation of their layer-by-layer self-assembled films with a hemicyanine dye. (1st June 2015) - Gao, Li-Hua; Zhang, Jin-Feng; Wang, Hui-Li; Lin, Xiao-Yan; Qi, Jian-Min; Wang, Ke-Zhi
Graphical abstract: Three electrostatic thin films based on a hemicyanine and [BW12 O40 ] 5−, [PW12 O40 ] 3− and [PMo12 O40 ] 3− have been reported. Variations of POMs in these films were found to strongly affect film-forming, visible absorption optical, and photoelectric conversion properties. [BW12 O40 ] 5− and [PW12 O40 ] 3−, based monolayer films exhibited significant cathodic photocurrent densities of 4.58-4.90 A/cm 2, while other two films gave weak photocurrent densities. Relationship between the POM compositions and photoelectric performance is expolored. Highlights: Three electrostatic thin films of hemicyanine with three polyoxometalates (POMs). Visible absorption maxima were strongly affected by POMs. Stable photocurrents that were differed by over 7 folds depending on POMs. Photocurrent difference is related with LUMOs of POMs. Abstract: A series of layer-by-layer electrostatically self-assembled films consisting of one of three Keggin-type polyoxometalates (POMs) of [BW12 O40 ] 5−, [PW12 O40 ] 3− and [PMo12 O40 ] 3−, and a hemicyanine of ( E )-1, 1′-methylenebis(4-(4-(dimethylamino)styryl)pyridinium)bromide (H 1 Br2 ) are prepared. The UV–vis absorption spectroscopy showed that the films were uniformly deposited with the visible absorption bands for the hemicyanine being bathochromically shifted with respect to the H 1 Br2 aqueous solution to different extents depending on POMs. The (POMs/H 1 ) n films exhibited stable photocurrents that were differed by over 7 folds depending on POMs as irradiated with white light. The effects of applied bias voltages, electron acceptor added in the electrolyte, and layer numbers of the films, irradiated light intensities, and the compositions of POMs on photocurrent generation of the films were discussed.